Cluster competence for higher resilience: A neo-institutional perspective on how firms from the Lusatian Energy Cluster cope with an external shock - Matthias Tomenendal; Hans Rüdiger Lange; Christian Raffer (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2020)
In former studies cluster firms have hardly proven to be more resilient to shocks than non-cluster firms. Yet, there is a lack of research on how cluster firms can achieve resilience. Based on a qualitative study of firms in the Eastern German Lusatian energy cluster we found that after a shock - a sudden decision on energy policy changes of the German federal government - cluster firms have replaced pre- by postshock institutional logics. Studied firms put more emphasis on further utilising core competences and demonstrate more openness to communicate inside and outside of the cluster. In essence, cluster firms change institutional logics for strengthened T-shaped cluster competences, which subsequently lead to higher resilience of cluster firms and clusters. By linking institutional logics to cluster resilience via cluster competences we provide a new perspective on how cluster firms can be resilient in the face of a shock. – – In früheren Studien haben sich Cluster-Firmen kaum als widerstandsfähiger gegenüber Schocks erwiesen als Nicht-Cluster-Firmen. Dennoch gibt es einen Mangel an Forschung darüber, wie Clusterfirmen Resilienz erreichen können. Basierend auf einer qualitativen Studie von Firmen im ostdeutschen Lausitzer Energiecluster haben wir herausgefunden, dass nach einem Schock - einer plötzlichen Entscheidung über energiepolitische Änderungen der Bundesregierung - Clusterfirmen die institutionellen Logiken vor dem Schock durch die nach dem Schock ersetzen. Die untersuchten Firmen legen mehr Wert darauf, ihre Kernkompetenzen weiter zu nutzen und zeigen mehr Offenheit, innerhalb und außerhalb des Clusters zu kommunizieren. Im Wesentlichen verändern Cluster-Firmen institutionelle Logiken für gestärkte T-förmige Cluster-Kompetenzen, die in der Folge zu einer höheren Resilienz von Cluster-Firmen und Clustern führen. Indem wir institutionelle Logiken über Clusterkompetenzen mit der Resilienz von Clustern verknüpfen, bieten wir eine neue Perspektive darauf, wie Clusterfirmen angesichts eines Schocks resilient sein können.
Keywords: L14; L29; O43; R11; 330; neo-institutionalism; cluster resilience; cluster competences